Indomethacin in COVID-19, more than just NSAID - Sorour, Khaled; El-Menshawy, Hadeer (My University, 2021)
This article aims to direct some interest on the positive role that Indomethacin could play in COVID-19. We relied on available evidence from the present literature and results of few clinical trials. We first discussed briefly, the documented antiviral activity of Indomethacin on coronaviruses and other viruses then moved to talk about how it could control the exaggerated immune response frequently reported during SARS-CoV-2 infection through the modulation of the PPAR-γ & HIF-1α axis. At the end, we posted the results of some clinical trials that we consider promising. It is important to note that our article does not carry a specific recommendation for Indomethacin as a global treatment for COVID-19, but we do believe it deserves to be implemented in more clinical trials.
Keywords: COVID-19; Cytokines; HIF-1 alpha; Indomethacin; PPAR-gama; SARS-CoV-2